A Trivalent HSV-2 gC2, gD2, gE2 Nucleoside-Modified mRNA-LNP Vaccine Provides Outstanding Protection in Mice against Genital and Non-Genital HSV-1 Infection, Comparable to the Same Antigens Derived from HSV-1 - Kevin P. Egan; Sita Awasthi; Giulia Tebaldi; Lauren M. Hook; Alexis M. Naughton; Bernard T. Fowler; Mitchell Beattie; Mohamad-Gabriel Alameh; Drew Weissman; Gary H. Cohen; Harvey M. Friedman (Viruses, 2023)
HSV-1 disease is a significant public health burden causing orofacial, genital, cornea, and brain infection. We previously reported that a trivalent HSV-2 gC2, gD2, gE2 nucleoside-modified mRNA-lipid nanoparticle (LNP) vaccine provides excellent protection against vaginal HSV-1 infection in mice. Here, we evaluated whether this HSV-2 gC2, gD2, gE2 vaccine is as effective as a similar HSV-1 mRNA LNP vaccine containing gC1, gD1, and gE1 in the murine lip and genital infection models. Mice were immunized twice with a total mRNA dose of 1 or 10 µg. The two vaccines produced comparable HSV-1 neutralizing antibody titers, and surprisingly, the HSV-2 vaccine stimulated more potent CD8+ T-cell responses to gE1 peptides than the HSV-1 vaccine. Both vaccines provided complete protection from clinical disease in the lip model, while in the genital model, both vaccines prevented death and genital disease, but the HSV-1 vaccine reduced day two vaginal titers slightly better at the 1 µg dose. Both vaccines prevented HSV-1 DNA from reaching the trigeminal or dorsal root ganglia to a similar extent. We conclude that the trivalent HSV-2 mRNA vaccine provides outstanding protection against HSV-1 challenge at two sites and may serve as a universal prophylactic vaccine for HSV-1 and HSV-2.